Un manoscritto giuridico miniato tra la Badia Fiorentina ed il Portogallo del xv secolo: il codice Conventi Soppressi A 4 2554 della Biblioteca Nazionale Centrale di Firenze - Sofia Orsino (Clio@Themis)
A fifteenth-century Latin manuscript, kept at the Biblioteca Nazionale Centrale in Florence and coming from the Benedictine monastery of Santa Maria (also known as Badia Fiorentina), contains the Repertorium iuris by Giovanni Nicola de Milis and seems to be the result of influences and contacts between Italy and Portugal. This article questions the enigmatic relationship between text and decoration; also, on the basis of an analysis of the illumination, combined with a codicological and palaeographical study, it reconstructs the context of production and the arrival of the codex in the Florentine monastery.